2012
DOI: 10.1590/s1677-55382012000100013
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional barbed suture versus standard monofilament for urethrovesical anastomosis during robotic assisted laparoscopic radical prostatectomy

Abstract: INTRODuCTIONRobotic-assisted laparoscopic prostatectomy (RALP) is a widely utilized, minimally invasive option for the treatment of prostate cancer and, in the short term, has demonstrated similar oncologic outcomes when compared with the open radical prostatectomy (1,2). The urethrovesical anastomosis (UVA) is a technically challenging aspect of RALP (3). Several UVA techniques have been described including a running suture anastomosis, interrupted suPurpose: V-Loc™180 (Covidien Healthcare, Mansfield, MA) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 27 publications
3
34
1
Order By: Relevance
“…A total of 12 studies, including three RCTs [9–11] (211 patients), nine cohort studies [12–20] (698 patients), and no case–control studies were found to fulfill the eligibility criteria. Table 1 presents the baseline characteristics of all studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies, including three RCTs [9–11] (211 patients), nine cohort studies [12–20] (698 patients), and no case–control studies were found to fulfill the eligibility criteria. Table 1 presents the baseline characteristics of all studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of the remaining 5 studies 10,11,14,17,19 indicated no significant differences in postoperative urinary leak (OR, 0.57; 95% CI, 0.20-1.67; Bladder Neck Stricture and Anastomosis Stricture Substantial heterogeneity was observed across the set of 5 studies reporting on bladder neck stricture and anastomosis stricture, which prohibited a meta-analysis. In the study by Polland et al, 16 …”
Section: Urinary Leak and Retentionmentioning
confidence: 98%
“…Ultimately, a total of 10 studies (comprising 378 cases and 369 controls) were included in our metaanalysis. [10][11][12][13][14][15][16][17][18][19] All the studies were published within the last 4 years, reflecting the increased application of this technique. Three studies were RCTs (LE, 2b) comparing BS and conventional sutures.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the efficacy and safety of this novel suture in gynecologic (31)(32)(33)(34)(35), urologic (36)(37)(38) and orthopedic surgery (39) have been reported. With respect to digestive surgery though, only a few studies, including our 2011 report of the first use of barbed sutures in gastrointestinal anastomoses, have proven the safety and suitability of barbed sutures in terms of anastomotic leakages or stenosis, but there have been no prospective studies for bowel anastomosis following LG for malignant disease.…”
Section: Discussionmentioning
confidence: 99%